Obstacles to developing cognitive creativity among secondary school students in Al-Baha region from the perspective of their teachers and ways to address them in light of Vision 2030 and contemporary global trends - Al-Zahrani, Ibrahim Mubarak Ahmed (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify the key barriers hindering cognitive creativity development among high school students in the Al-Baha region, as perceived by their teachers. It further sought to propose solutions in light of Saudi Vision 2030 and contemporary global educational trends. The study employed a descriptive-analytical survey methodology and utilized a questionnaire administered to a sample of 164 male and female high school teachers in Al-Baha. The findings revealed that the overall mean score of perceived barriers was 3.31, indicating a moderate level. Among the domains assessed, student-related barriers ranked highest (M = 3.49, high), followed by administrative structures (M = 3.39), teacher-related factors (M = 3.21), and subject matter characteristics (M = 3.16), all within the moderate range. Statistically significant differences were found based on gender, favoring female teachers, while no significant differences were observed based on teaching experience or academic qualification. Based on the results, a comprehensive framework was developed to address the identified challenges. The study recommends enhancing professional development programs for teachers and redesigning the high school learning environment to better foster creativity. It concludes with a proposed model outlining integrative roles for schools, teachers, and curricula in promoting cognitive creativity in alignment with Vision 2030.